2017
DOI: 10.3389/fpls.2017.01422
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analyses of Gene Expression Changes Triggered by Rhizoctonia solani AG1 IA Infection in Resistant and Susceptible Rice Varieties

Abstract: Rice sheath blight, caused by Rhizoctonia solani, is one of the most devastating diseases for stable rice production in most rice-growing regions of the world. Currently, studies of the molecular mechanism of rice sheath blight resistance are scarce. Here, we used an RNA-seq approach to analyze the gene expression changes induced by the AG1 IA strain of R. solani in rice at 12, 24, 36, 48, and 72 h. By comparing the transcriptomes of TeQing (a moderately resistant cultivar) and Lemont (a susceptible cultivar) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
56
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 91 publications
2
56
1
Order By: Relevance
“…The study also reported improved sheath blight tolerance in transgenic rice plants overexpressing the RGB1 gene. The involvement of secondary messengers of rice in immune responses to R. solani has been reported in some comparative transcriptome and proteomic studies (Karmakar et al , ; Zhang et al , ). Several calcium/calmodulins signalling pathway genes ( OsCPK10 , OsCML16 , OsCML26 , OsCML27 , OsCML 31, OsCam1‐1 ) were differentially regulated at different time points after infection in response to ShB infection (Zhang et al , ) indicating the involvement of the secondary messengers, Ca2+ and calmodulin.…”
Section: Molecular Interplay Between Rice and R Solanimentioning
confidence: 96%
See 3 more Smart Citations
“…The study also reported improved sheath blight tolerance in transgenic rice plants overexpressing the RGB1 gene. The involvement of secondary messengers of rice in immune responses to R. solani has been reported in some comparative transcriptome and proteomic studies (Karmakar et al , ; Zhang et al , ). Several calcium/calmodulins signalling pathway genes ( OsCPK10 , OsCML16 , OsCML26 , OsCML27 , OsCML 31, OsCam1‐1 ) were differentially regulated at different time points after infection in response to ShB infection (Zhang et al , ) indicating the involvement of the secondary messengers, Ca2+ and calmodulin.…”
Section: Molecular Interplay Between Rice and R Solanimentioning
confidence: 96%
“…The involvement of secondary messengers of rice in immune responses to R. solani has been reported in some comparative transcriptome and proteomic studies (Karmakar et al , ; Zhang et al , ). Several calcium/calmodulins signalling pathway genes ( OsCPK10 , OsCML16 , OsCML26 , OsCML27 , OsCML 31, OsCam1‐1 ) were differentially regulated at different time points after infection in response to ShB infection (Zhang et al , ) indicating the involvement of the secondary messengers, Ca2+ and calmodulin. Wall‐associated kinases (WAKs) are known to bind several types of pectin, including oligomer generated by pathogen‐mediated cell wall degradation, and involved in pathogen‐responsive signal transduction pathways (Kohorn and Kohorn, ).…”
Section: Molecular Interplay Between Rice and R Solanimentioning
confidence: 96%
See 2 more Smart Citations
“…The differences in the molecular basis between the interaction of resistant and susceptible cultivars or species with the pathogens (23,24) suggests that RNA-Seq is an ideal tool to dissect the resistance mechanism of host plants (25).…”
mentioning
confidence: 99%